GREEN REVOLUTION AND SOCIAL CHANGE IN SUBAK SUSUAN, KARANGASEM, BALI - Eddy, I Wayan Tagel (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2017)
This study aims to determine the social changes in Subak Susuan Karangasem Bali as a result of the implementation of green revolution (revolusi hijau). The method used observation, in-depth interviews equipped with interview guides, recording devices, cameras and stationery. Sampling is done by purposive or direct appointment to a person who is considered to know and be directly involved in the event.The results show that the green revolution has digraded various types of local rice seeds and simultaneously marginalizes local wisdom resulting in social change. Agricultural homogeneity, which in turn has diminished farming culture, professional social organization such as sekaa numbeg, sekaa manyi, sekaa metekap began to decrease and patron client bond is getting worse. The government is advised to pay attention to the values ??of local wisdom that guides the life of farming in Subak Susuan.